PENINGKATAN KETERAMPILAN NASYIATUL AISYIYAH KABUPATEN SINTANG DALAM PEMBUATAN TEHBAWANG BERLIAN (Eluetherine Palmifolia (L) Merr.) SEBAGAI SUMBER PENDAPATAN ALTERNATIF - Wulan Purnama Sari; Yeni Yeni; Hurul Aini (Universitas Mataram, 2026)
This community service activity is intended to improve the skills and financial independence of members of Nasyiatul Aisyiyah in Sintang Regency by teaching them how to make onion tea from the diamond lily (Eleutherine palmifolia (L.) Merr.) as a profitable herbal product. A native plant of West Kalimantan known for its many health benefits, including lowering blood pressure and blood sugar levels and boosting immunity, is known as diamond onion. This potential highlights the importance of developing processing methods into ready-to-use products with commercial value. Technical training on making herbal tea (slicing, drying, and packaging) and product marketing support thru simple community-based strategies are part of the activity methods. The results of the activity show an improvement in participants' skills in the production process and the creation of diamond onion tea products in ready-to-sell boxes. This activity not only enhances technical skills but also fosters the entrepreneurial spirit of women, introduces the potential of local plants, and opens up sustainable alternative income opportunities for the community, particularly Nasyiatul Aisyiyah of Sintang Regency.